Robust coordinated transmission for cooperative small cell networks. Issue 16 (1st November 2016) - Kim, Yonggang; Park, Kyung‐Joon; Park, Daeyoung; Lim, Hyuk
Abstract : Within a macrocell with a large coverage area, multiple small cells are deployed such that each small cell base station (SBS) supports wireless service demands from user equipments (UEs). Each UE can be simultaneously served by multiple SBSs for quality of service (QoS) enhancement. When there exist hotspot areas with a number of UEs, the SBSs near the hotspot areas may experience a higher resource utilisation level than those outside of the hotspot areas, resulting in a shortage of available resources. The authors propose a robust resource‐utilisation‐based coordinated transmission for heterogeneous networks with a locally different level of traffic demands. In the utilisation‐based coordinated transmission, low‐utilisation SBSs with a small number of UEs are selected to serve a newly joining UE because they have more capacity to serve requests with bursty traffic demand. They further formulate the selection of cooperative SBSs as a robust optimisation problem in order to ensure that UEs have sufficiently high signal‐to‐interference‐plus‐noise ratios, even with channel estimation inaccuracy and strong interference from non‐cooperative SBSs. The simulation results indicate that the proposed method guarantees robust and efficient service performance in heterogeneous small cell networks.